Antibacterial Properties of Alkaloid Extracts from Callistemon citrinus and Vernonia adoensis against Staphylococcus aureus and Pseudomonas aeruginosa. (20th January 2016) - Mabhiza, Donald; Chitemerere, Tariro; Mukanganyama, Stanley
Abstract : The development of new antibiotics from new chemical entities is becoming more and more expensive, time-consuming, and compounded by emerging strains that are drug resistant. Alkaloids are plant secondary metabolites which have been shown to have potent pharmacological activities. The effect of alkaloids from Callistemon citrinus and Vernonia adoensis leaves on bacterial growth and efflux pump activity was evaluated on Staphylococcus aureus and Pseudomonas aeruginosa . At a concentration of 1.67 mg/mL, the alkaloids inhibited bacterial growth with comparable effects to ampicillin, a standard antibiotic. The alkaloids from C. citrinus were the most potent against S. aureus with an MIC of 0.0025 mg/mL and MBC of 0.835 mg/mL. It was shown that effects on P. aeruginosa by both plant alkaloids were bacteriostatic. P. aeruginosa was most susceptible to drug efflux pump inhibition by C. citrinus alkaloids which caused an accumulation of Rhodamine 6G of 121% compared to the control. Thus, C. citrinus alkaloids showed antibacterial activity as well as inhibiting ATP-dependent transport of compounds across the cell membrane. These alkaloids may serve as potential courses of compounds that can act as lead compounds for the development of plant-based antibacterials and/or their adjunct compounds.